Implementation consensus algorithm and leader-follower of multi-robot system formation - Noval Lilansa; Muhammad Nursyam Rizal; Pipit Anggraeni; Nur Jamiludin Ramadhan (SINERGI, 2023)
Robot technology has recently been applied to many applications to help human activities. Mobile Robot is one of the most flexible robot technology. This research uses a mobile robot designed using an omnidirectional wheel for the movement mechanism. Coordination and control of multi-robots can be assigned to perform any task from a different kind of field. Therefore, this paper aims to develop a multi-robot system to form a formation to do the task. The multi-robot system consists of three units Mobile Robot. The formation system will be built based on a coordinate point determined by a consensus point. The leader-follower topology is used to determine the orientation of the robot. ROS (Robot Operating System) is used as middleware to create a multi-robot system. The Open Base package in Gazebo Simulator is also used to simulate the movement of the multi-robot. From three test scenarios, this research results show that all the robots can do and follow the tasks simulated in the Gazebo with an average accuracy of 88.14%. Furthermore, no feedback from the robot to the Gazebo Simulator affects the robot's accuracy average below 90%.